Career-switchers in career and teaching education school system: what drives them to remain in teaching? - Omar, Muhd Khaizer; Self, Mary Jo; Cole, Ki Lynn Matlock (Human Resource Management Academic Research Society, 2017)
Teacher attrition embarks seriousness in the teaching arena, whereby research reported a number of teachers leaving their profession in their early years of their profession. Often, this number does not represent CTE teachers’ scarcity in depicting teachers’ dropout. This realm contributes to a deeper understanding and reasons for us to carry out research pertaining to CTE teachers. The nature of the study was coming from a mixed-methods design, however, this article mainly presents findings from the qualitative section. Five hundred and eighty-one CTE teachers responded to the online survey and out of this number, only 272 were identified as career-switchers. Based upon constant comparative methods, there are three themes emerged from the study. The themes are passionate in making a difference of students, teaching as a compassionate job, and teaching as a chosen occupation. Implications of the results and future direction presented in this article contribute to a deeper understanding in cultivating the spirit and values behind the teaching profession among CTE teachers. Valuing the role of CTE teachers in the CTE educational system will ensure the continuity of supply of semi-skilled employee from the industry. For this reason, understanding their reasons of staying as teachers will assist them not only to survive in teaching, but also enjoying the profession altogether.